Informed consent in clinical research in France: assessment and factors associated with therapeutic misconception. Issue 9 (29th August 2008) - Durand-Zaleski, I S; Alberti, C; Durieux, P; Duval, X; Gottot, S; Ravaud, Ph; Gainotti, S; Vincent-Genod, C; Moreau, D; Amiel, P
Abstract : Background: Informed consent in clinical research is mandated throughout the world. Both patient subjects and investigators are required to understand and accept the distinction between research and treatment. Aim: To document the extent and to identify factors associated with therapeutic misconception in a population of patient subjects or parent proxies recruited from a variety of multicentre trials (parent studies). Patients and methods: The study comprised two phases: the development of a questionnaire to assess the quality of informed consent and a survey of patient subjects based on this questionnaire. Results: A total of 303 patient subjects or parent proxies were contacted and 279 questionnaires were analysed. The median age was 49.5 years, sex ratio was 1 and 61% of respondents were professionally active. Overall memorisation of the oral or written communication of informed consent was good (69–97%), and satisfaction with the process was around 70%. Therapeutic misconception was present in 70% of respondents, who expected to receive better care and ignored the consequence of randomisation and treatment comparisons. This was positively associated with the acuteness and severity of the disease. Conclusion: The authors suggest that the risk of therapeutic misconception be specifically addressed in consent forms as an educational tool for both patients and investigators.